PENGARUH PEMBERIAN LAYANAN PENGUASAAN KONTEN TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA KELAS X SMAN 10 PEKANBARU - Rahmah, Mutia; ', Rosmawati; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : One of guidance and counceling teacher’s duty is to do activity or give material that could growing to develop student’s learning motivation trough several serving guidance of counceling activities. One of it called mastering of content. The purpose of this research is to get data about level of student’s learning motivation before and after giving mastering of content control service, and notice the difference in learning motivation after mastering of content service and given the magnitude of the influence that the service given to increase content Mastery Learning motivation of students of class X SMAN 10 Pekanbaru. Using sampling purposive teknique it’s get’s 72 sample of student’s. To received data it the question’s form. Based on research that have done it receive data before giving mastering of content service learning motivation students less than (44%). In fact after disseminating the second question’s form the student learning motivation is increase higher (58%). Based on results of calculation t tests obtained results that thitung (17,75) is larger than ttabel (1,960) with 5% error level, could be interpreting that Ha is received. To see the level of the influence that given by mastering of content service to increase Learning motivation of students of class X SMAN 10 Pekanbaru. It measured from square the interpretation asses correlation coefficient (r2) 0.49 (medium). Which means that the mastery content service gives influence to the improvement of student learning motivation of 49%, whereas 51% is affected by other factors that are contained inside as well as the environment of students. So based on research conducted by the author to the conclusion that can be drawn, awarding the services exert influence content mastery to increase learning motivation of students of class X SMAN 10 Pekanbaru.Keywords: motivation learning, service content mastery, guidance and counseling